ANALISIS PENGARUH ENTERTAIMENT, INFORMATIVENESS, IRRITATION, DAN CREDIBILITY TERHADAP ADVERTISING VALUE DAN CONSUMERS ATTITUDE - Sholicha, Alfina; Novandari, Weni (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
Mobile marketing offers great opportunities for businesses wich can comunicate directly with their consumers without time or location barriers. Many factors influencing advertising message of mobile marketing still need further investigation. Mobile advertising addresses consumers with induvidualized advertising messages via mobile device. In this case, in order to know the effectivenees of advertising via SMS, it can be traced by looking at the advertising value. This research attempts to analyse the influence of entertaiment, informativeness, irritation, and credibility toward advertising value, and advertising value toward consumers attitude on advertising via SMS. The result show that entertaiment, informativeness, and credibility have positive influence and irritaion have negative influence toward advertising value. Advertising value have positif influence toward consumers attitude for advertising via SMS.